XIth International Congress on Thrombosis and Haemostasis 1987
DOI: 10.1055/s-0038-1644764
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor Biochemical and Clinical Aspects

Abstract: Plasminogen activator (PAs) are enzymes that convert the zymogen plasminogen into the trypsin-like protease plasmin, which degrades extracellular matrix proteins and fibrin in the course of fibrinolysis, embryogenesis, tissue remodeling and in tumor metastasis. Plasminogen activator inhibitors (PAIs) are important modulators of PA activity. Several proteins have been identified which inhibit at fast rates urokinase (u-PA) and tissue-type PA (t-PA). In the order of inhibition rate constants these are: a) PAI-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
3

Year Published

1990
1990
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 0 publications
0
34
0
3
Order By: Relevance
“…In this study, aspirin was shown to inhibit AA-induced platelet PAI-1 secretion and was also shown to lower the plasma levels of PAI-1 at 2 h after aspirin administration, which per sisted in part for up to 24 h. These data might suggest at least in part some explanation for impressive clinical benefits of aspirin, since high plasma levels of PAI-1 have been consid ered as a risk factor in various thromboem bolic disorders [12],…”
Section: Discussionmentioning
confidence: 85%
“…In this study, aspirin was shown to inhibit AA-induced platelet PAI-1 secretion and was also shown to lower the plasma levels of PAI-1 at 2 h after aspirin administration, which per sisted in part for up to 24 h. These data might suggest at least in part some explanation for impressive clinical benefits of aspirin, since high plasma levels of PAI-1 have been consid ered as a risk factor in various thromboem bolic disorders [12],…”
Section: Discussionmentioning
confidence: 85%
“…Numerous studies have correlated decreased plasma fibrinolytic activity with elevated PAI-1 in patients with septicaemia and during postoperative recovery [10]. Similarly, a positive correlation has been reported between plasma PAI-1 levels and inflammatory protein [5].…”
Section: Discussionmentioning
confidence: 89%
“…The discordance between the two may have resulted from different assay methods used for the determination of PAI-1 . PAI-1 is present in plasma not only as free PAI-1 but also as PAI-I complexed to t-PA and only a free, active form possesses the inhibitory capacity [34]. When plotted by disease categories, the magnitude of elevations of FbDP and TDP was the most prominent in patients with acute hepatitis (Fig.…”
Section: Discussionmentioning
confidence: 98%